Return to Work (RTW) challenges and mental health issues among unemployed persons in Selangor - R., Aidil Wajdi; R., Irniza; S. I., Sharifah Norkhadijah; Z. A., Emilia (Faculty of Medicine and Health Sciences, UPM, 2023)
Inability to find a job for a long time due to Covid-19 factor may lead to mental health issues in individual due to many reasons. Objective: This research aims to explore the association between return-to-work (RTW) challenges and mental health issues among 166 unemployed workers in Selangor. Method: A cross-sectional study was conducted using snowball sampling method. A self-administered questionnaire to measure RTW challenges, anxiety (GDA-7) and depression (PHQ-9) was used in this study. Result: Majority of the respondents is male (61.4), aged between 20 to 34 years old, and have SPM (29.5) and bachelor’s degree (29.5). Most respondents experienced moderate levels of RTW challenges. The most claimed challenges for them to RTW are lack of work experiences (92), followed by lack of social support (86), lack of skill (85), current commitment (e.g., taking care of elderly/studying) (74), and distances to workplace (72). The prevalence of anxiety and depression were 81.3 and 71.1 respectively. The were significant correlation between RTW challenges with both anxiety (τ = .343, p < 0.001) and depression (τ = .343, p < 0.001). In multivariate analyses, RTW challenges, level of education, and gender accounted for a significant 35.7 of the variability in anxiety and 24.2 of the variability in depression. Conclusion: The prevalence of mental health issues is high among respondents and is proven to be associated with RTW challenges. Hence, prompt intervention strategies need is needed to support mental health of unemployed workers by all related parties including government, policy makers and employers.